Strategies to Enhance Employee Loyalty: The Role of Leadership Style, Job Satisfaction, and Overtime - Agung Budi; Siti Rahma Octavia; Enawar (IECON: International Economics and Business Conference, 2025)
This study aims to analyze strategies for improving employee loyalty through the roles of leadership style and job satisfaction, with overtime serving as a moderating variable. The background of this research is the high employee turnover rate in Indonesia, which negatively affects organizational stability and productivity. A quantitative approach with a causal design was employed, using data collected through questionnaires distributed to 74 permanent employees of PT XYZ Serpong Branch. Data analysis was conducted using Structural Equation Modelling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS software. The findings reveal that leadership style has a positive and significant effect on job satisfaction, but no direct effect on employee loyalty. Job satisfaction is a significant mediating variable in the relationship between leadership style and employee loyalty. In addition, overtime significantly influences job satisfaction and indirectly affects employee loyalty through job satisfaction. However, overtime does not moderate the relationship between leadership style and either job satisfaction or employee loyalty. The state of the art of this research lies in its integrative model, which combines three key dimensions in human resource management—leadership, job satisfaction, and overtime—and applies a PLS-SEM approach to simultaneously examine mediation and moderation effects. This study contributes to the literature by demonstrating that employee loyalty is more effectively enhanced through the mediating role of job satisfaction rather than direct leadership intervention or overtime practices. Nevertheless, this study is limited to analyzing the influence of leadership style, job satisfaction, and overtime on employee loyalty at PT XYZ Serpong Branch with a sample of 74 permanent employees. The analysis approach uses PLS-SEM through SmartPLS, and findings are contextual, not intended for generalization across organizations or sectors.